Research Trends on Digital Entrepreneurship with Islamic Values: Bibliometric Analysis (2012-2022) - Acep Supriadi; Muhammad Nur (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The impact of digital transformation on the shape of business operations around the world cannot be understated. Yet, the Islamic digital economy era remains in its infancy, and the challenges that it faces are still left unanswere. Nonetheless Entrepreneurship learning is still a subject that is considered difficult for students because it is considered incompatible between theory and practice. Ease of access to information technology in the era of the industrial revolution 4.0 is considered to be one of the hopes in achieving learning success, especially in entrepreneurship courses. A business opportunity made possible by the use of technology platforms and other information communication technologies is known as digital entrepreneurship. The idea of digital entrepreneurship publication, which displayed the big picture utilizing data from all countries, has not yet been thoroughly researched. This study uses bibliometric analysis to visually map all scholarly papers in the topic of digital entrepreneurship that have been indexed by Scopus. This study makes use of the analysis capabilities of Scopus programs and makes use of VOSviewer to show bibliometric networks. This study adds keywords for digital entrepreneurship to the Scopus database, which contains 335 scholarly papers published globally between 2012 and 2022. Increasing numbers of worldwide papers in the have been identified to exhibit patterns and trends based on this investigation: entreprenuership, entreprenuer, socialentrepenuership, social networking, sustainbility and digitallization.